PREVALENSI GLAUKOMA AKIBAT DIABETES MELITUS DI POLIKLINIK MATA RSUP PROF. DR. R. D. KANDOU MANADO - Allorerung, Risky N.; Saerang, Josefien S. M.; Rares, Laya M. (Universitas Sam Ratulangi, 2015)
Abstract: Glaucoma is a common group of diseases characterized by optic neuropathy typically, related with loosing of a field visual of vision. A very high intraocular pressure is one of the primary risk factors. Glaucoma can be caused by systemic diseases or local diseases of the eye. One of the systemic disorders that can lead to glaucoma is diabetes mellitus (DM). This study aimed to obtain the prevalence of glaucoma caused by DM in the Eye Clinic Prof. Dr. R. D. Kandou Hospital Manado from January to December 2013. This was a descriptive retrospective study. The results showed that of 15 patients who got glaucoma caused by DM there were 10 (66.7%) females and 5 (33.3%) males. Based on age group, the mean age group of elderly which was also the most frequent one was 61-70 years with 7 patients (46.7%). The most frequent type of DM was type 2 with 14 patients (93.3%) meanwhile DM type only 1 patient (6.7%). There were 12 patients (80%) with uncontrolled DM who were more prone to suffer from glaucoma than the 3 patients (20%) with controlled DM.Keywords: glaucoma, diabetic of mellitusAbstrak: Glaukoma adalah kelompok penyakit yang ditandai oleh neuropati optik yang khas, serta berhubungan dengan hilangnya lapang pandangan penglihatan. Tekanan intraokuli yang sangat tinggi merupakan salah satu faktor resiko primer. Glaukoma dapat disebabkan oleh penyakit sistemik maupun penyakit lokal pada mata. Kondisi kelainan sistemik yang dapat memicu terjadinya glaukoma salah satunya ialah diabetes mellitus (DM). Penelitian ini bertujuan mengetahui prevalensi glaukoma akibat DM di Poliklinik Ilmu Kesehatan Mata BLU RSUP Prof. Dr. R. D. Kandou Manado periode Januari - Desember 2013. Penelitian ini bersifat deskriptif retrospektif. Hasil penelitian menunjukkan dari 15 pasien mengalami glaukoma akibat DM yang berjenis kelamin perempuan lebih banyak yaitu 10 pasien (66,7%) sedangkan laki-laki 5 pasien (33,3%). Berdasarkan kelompok umur, rerata umur lansia dan yang paling banyak yaitu umur 61-70 sebanyak 7 pasien (46,7%). Dilihat dari Tipe DM, DM tipe 2 yang paling banyak yaitu 14 pasien (93,3%) dan DM tipe 1 hanya satu pasien (6,7%). DM tidak terkontrol ditemukan pada 12 pasien (80%) lebih mudah mengalami glaukoma di bandingkan diabetes terkontrol pada 3 pasien (20%).Kata kunci: glaukoma, diabetes melitus